Pengaruh Kepemimpinan Transformasional, Kompetensi, Kompensasi Finansial Terhadap Motivasi Kerja Dan Kinerja Karyawan (Studi Pada PT Telkom Cabang Banjarmasin, Kantor Grha Witel Kalsel) - Yizreel Junus Kende; Hairudinor Hairudinor; Nurul Wahyuni (JURNAL BISNIS DAN PEMBANGUNAN, 2016)
This study aims to examine how much influence Transformational Leadership, Kompensi and Financial Compensation Against Employee Motivation and Performance. Each organization is always in need of employees to run its operations. Given the organization's employees is an important asset, so many things that need to be associated with an increased performance. The good performance is one of the objectives of the organization in achieving high productivity. Thus achieving a good performance can not be separated from human resource quality is also good. As with any other organization, PT Telkom Branch of Banjarmasin, South Kalimantan Witel Office requires qualified human resources in order to support, to realize the vision and mission of the organization's goals. The conclusion of this study are: the performance of employees of PT Telkom Branch of Banjarmasin, South Kalimantan Witel Grha Office. Keywords: Transformational Leadership, Competencies, Financial Compensation, Employee Motivation and Performance.